ChemInform Abstract: Electron Carrier‐mediated Room Temperature Ferromagnetism in Anatase (Ti, Co)O2. Issue 7 (18th February 2014) - Fukumura, Tomoteru; Yamada, Yoshinori; Ueno, Kazunori; Yuan, Hongtao; Shimotani, Hidekazu; Iwasa, Yoshihiro; Gu, Lin; Tsukimoto, Susumu; Ikuhara, Yuichi; Kawasaki, Masashi
Abstract Review: 64 refs.